Performance of microwave cured C/SH particle modified glass fibre prepregs - Chew, Brandon Yuen (2016)
In today’s world where technology is advancing at such a tremendous rate, industries are constantly growing and looking for new methodologies to manufacture composites at a cheaper and faster rate. Traditional methods such as Autoclave curing, have a long curing time and consumes a lot of energy, hence it becomes costly. Microwave curing has been earmarked as an alternative to Autoclave curing due to its shorter curing time and lower consumption of energy. In this project, an attempt to manufacture dispersed core shell polymer (C/SH) particle modified Glass Fibre Prepreg (GFRP) was successfully achieved using controlled process parameters (pressure, time and heat) during microwave curing. Dynamic Mechanical Analysis (DMA), Vibration and Flexural Testing were carried out on the manufactured specimens to study the damping and flexural properties of microwave cured GFRP and C/SH particle modified GFRP. The results of the two variants were compared, and also with those cured thermally. The addition of C/SH particles has shown an improvement in damping and flexural properties. C/SH particle modified GFRP exhibited better energy dissipation, better elastic properties and higher flexural strength. The optimal areal weight per interface (AWI) for C/SH particles after each test was established as 40g/m2. The 40g/m2 specimen showed an increase of 21.5% in tan δ value, and 15.9% in flexural strength, compared to the specimen with no particles. The damping properties of microwaved cured C/SH particle modified GFRP were comparable or even better than that of one with no particles.